Bullying and truancy amongst school-going adolescents in Timor-Leste: results from the 2015 global school-based health survey. Issue 1 (January 2022) - Owusu, Derrick Nyantakyi; Owusu Ansah, Kenneth; Dey, Nutifafa Eugene Yaw; Duah, Henry Ofori; Agbadi, Pascal
Abstract: Introduction: Studies in Southeast Asia found that bullying commonly occurred among students, and it has a detrimental impact on their school attendance. However, there is a paucity of literature in Timor-Leste on the association between bullying and truancy. Therefore, this study examined the association between bullying and truancy among Timor-Leste school-going adolescents. Methods: We used the 2015 Timor-Leste Global School-based Student Health Survey (GSHS) dataset to examine our hypothesis in logistic regression models for both full adolescents ( N = 3609) and gender stratified samples. The models further controlled for other sociodemographic variables. Statistical significance was pegged at p ≤ 0.05, and the analyses were performed in Stata version 14. Results: About 28% [95% CI:25.7, 30.8] and 36% [95% CI:33.5, 39.5] of school-going adolescents had experienced bullying and truancy, respectively. In-school adolescents who were bullied were more likely to be truant in school even after controlling for the effects of sex, age, grade in school, food insecurity, current substance use, number of friends, colleague support, and parental involvement. This relationship remained significant in the full and gender stratified models. Additionally, school-going adolescents who were currently using substances were truant. Males who were in a physical fight while females who were physically attacked were more likely to be truant. Conclusion: The study showed that bullying was related to truancy among school-going adolescents in Timor-Leste. Implementation of interventions such as Project START (Stop Truancy and Recommend Treatment) to curtail the incidence of bullying, regulation of current substance use, creating an enabling environment to reduce physical fights, and attacks will significantly reduce the rate of truancy among school-going adolescents in Timor-Leste. Abstract : Bullying; Truancy; School-going adolescents; Timor-leste; Logistic regression.